A five-year follow-up study of neurocognitive functioning in bipolar disorder - Santos, José Luis; Aparicio, Ana; Bagney, Alexandra; Sánchez-Morla, Eva María; Rodríguez-Jiménez, Roberto; Mateo, Jorge; Jiménez-Arriero, Miguel Ángel (Bipolar disorders, 2014)
Objectives Cognitive dysfunction in bipolar disorder has been well‐established in cross‐sectional studies; however, there are few data regarding the longitudinal course of cognitive performance in bipolar disorder. The aim of this study was to examine the course of cognitive function in a sample of euthymic patients with bipolar disorder during a five‐year follow‐up period. Methods Eighty euthymic outpatients with a DSM‐IV diagnosis of bipolar disorder and 40 healthy control comparison subjects were neuropsychologically assessed at baseline (T1) and then at follow‐up of five years (T2). A neurocognitive battery including the main cognitive domains of speed of processing, working memory, attention, verbal memory, visual memory, and executive function was used to evaluate cognitive performance. Results Repeated‐measures multivariate analyses showed that progression of cognitive dysfunction in patients was not different to that of control subjects in any of the six cognitive domains examined. Only a measure from the verbal memory domain, delayed free recall, worsened more in patients with bipolar disorder. Additionally, it was found that clinical course during the follow‐up period did not influence the course of cognitive dysfunction. Conclusions Cognitive dysfunction that is characteristic of bipolar disorder is persistent and stable over time. Only dysfunction in verbal recall was found to show a progressive course that cannot be explained by clinical or treatment variables.